2020
DOI: 10.9734/ejmp/2020/v31i830261
|View full text |Cite
|
Sign up to set email alerts
|

Aloe vera (L.) Burm. F. as a Potential Anti-COVID-19 Plant: A Mini-review of Its Antiviral Activity

Abstract: Aims: A novel β-coronavirus (2019-nCoV) has become a pandemic affecting hundreds of thousands of people worldwide. Since there is no effective treatment, the need of finding alternative methods which can help to curb this pandemic is urgent. This study aims to review the literature on the virucidal and cytotoxic properties of Aloe vera, one of the most studied plants considered as a nutraceutical in order to propose it as an alternative solution against COVID-19. Methodology: The literature review was ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 19 publications
0
31
0
5
Order By: Relevance
“…It has various medicinal properties and therefore, it is used in various pharmaceutical applications. Antiviral and antibacterial effects of Aloe vera has also been reported in the literature [ 46 , 47 ]. Aloin and aloe-emodin are the key molecules for the antiviral activity of Aloe vera .…”
Section: Ecofriendly Hand Hygienementioning
confidence: 97%
See 1 more Smart Citation
“…It has various medicinal properties and therefore, it is used in various pharmaceutical applications. Antiviral and antibacterial effects of Aloe vera has also been reported in the literature [ 46 , 47 ]. Aloin and aloe-emodin are the key molecules for the antiviral activity of Aloe vera .…”
Section: Ecofriendly Hand Hygienementioning
confidence: 97%
“…Aloin and aloe-emodin are the key molecules for the antiviral activity of Aloe vera . These molecules kill the enveloped viruses including SARS-CoV-1, influenza, and HIV viruses either by destructing the lipid envelope of the virus or inhibiting the viral replication [ 47 ]. All these properties make it an attractive choice to be a key component in a non-alcoholic hand rub sanitizer.…”
Section: Ecofriendly Hand Hygienementioning
confidence: 99%
“…Indeed, the ligand 1 or chrysin has anti-in ammatory, antibacterial and antioxidant activities [44][45], while ligand 2 or kaempferol exhibits antitumor, antioxidant and anti-in ammatory capabilities [46]. In fact, our previous studies showed that aloe vera represents potential treatment for COVID-19 [47], and three of its phytochemicals were identi ed as potential inhibitors of SARS-CoV-2 main protease, in which two compounds exhibit antiin ammatory effect [5]. The anti-in ammatory activity of luteolin in experimental animal models was reported by Ziyan and co-workers [48], and recently, a study by Lesjak and co-authors showed antioxidant and anti-in ammatory activities of quercetin and its derivatives [49].…”
Section: Scrutiny Of Toxicity Outcomes Inmentioning
confidence: 98%
“…Aloe vera also contains zinc, which has the ability to inhibit the replication of retroviruses including SARS-CoV- 1 [ 94 ]. Mpiana and co-workers are convinced that Aloe vera extract rich in zinc and its secondary bioactive metabolites could be used in the management of COVID-19 owing to their ability to attenuate expression of pro-inflammatory factors that induce acute respiratory distress and by strengthening the immune system [ 95 ]. Gyebi and co-workers screened 62 alkaloids and 100 terpenoid bioactive natural products derived from the native African medicinal plants as potential inhibitors of coronavirus 3-chymotrypsin-like protease (3CL pro ) using in silico approach.…”
Section: Potential Of Medicinal Plants Against Covid-19mentioning
confidence: 99%